Suicidal ideation and attempt of older women in Northeastern Brazil - Raimunda Magalhães da Silva; Girliani Silva de Sousa; Luiza Jane Eyre de Souza Vieira; José Manuel Peixoto Caldas; Maria Cecília de Souza Minayo
ABSTRACT Objective: to associate the life experiences of older women from the Northeast of Brazil with their suicidal ideation and attempts. Method: Qualitative study with fourteen older adults from Piripiri (PI), Teresina (PI), Fortaleza (CE) and Recife (PE) who were interviewed between November 2013 and July 2014. The organization of data originated the themes: experiences of abuse throughout their lives; marital fractures and social isolation; weakened motherhood. Results: The women were born and lived most of their life in the countryside, amid poverty and social exclusion. They had a history of abuse, physical and sexual violence, perpetrated by intimate partners and/or family members. They experienced social isolation, weakened emotional bonds and several suicide attempts. Final considerations: The life of these older women was affected by traumatic events that enhanced feelings of hopelessness, depressive symptoms and the absence of a plan for the future, making them consider suicide as a way to anticipate death.